SYNESTHETIC METAPHORS IN WILLIAM BUTLER YEATS’ POETRY - Japaridze, Rusudan (Online Journal of Humanities ETAGTSU, 2016)
This paper discusses the phenomenon of synesthetic metaphors in William Butler Yeats‟ poetic works. The revealed synesthetic metaphors have been analysed according to the Conceptual Metaphor Theory (CMT) which forms the theoretical basis of the research. In 15 randomly selected poems, 15 samples of synesthetic metaphor have been encountered. After analysing and calculating the percentage of the evidenced examples combining different perceptual categories, visual + tactile type has turned out to be the most frequently used combination of modalities. As the results have shown all the categories of perception are included in the discussed examples except the olfactory one. Full Text (PDF)